2020
DOI: 10.1091/mbc.e20-02-0127
|View full text |Cite
|
Sign up to set email alerts
|

RAC1 induces nuclear alterations through the LINC complex to enhance melanoma invasiveness

Abstract: RHO GTPases are key regulators of the cytoskeletal architecture, which impacts on a broad range of biological processes in malignant cells including motility, invasion and metastasis, thereby affecting tumor progression. One of the constrains during cell migration, is the diameter of the pores through which cells pass. In this respect, the size and shape of the nucleus poses a major limitation. Therefore, enhanced nuclear plasticity can promote cell migration. Nuclear morphology is determined in part through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Rac1-regulated actin dynamics contribute to nuclear membrane organization, which in turn can have an impact on LMNA/C-emerin complex distribution, supporting direct crosstalk between nuclear actin network changes and lamin cortex integrity and remodeling; further, Rho GTPase control of the cytoskeleton is an additional input, through the LINC complex, onto nuclear mechanoadaptation. Current investigations demonstrate that Rac1 induces nuclear alterations through microtubules and LINC complex to promote an invasive phenotype in melanoma cells [168]. Rho GTPases are also involved in the specific control of the perinuclear actin cap, a specialized cytoskeletal structure of fibers contacting the nucleus that regulates both nuclear morphology and re-orientation during front-rear polarization.…”
Section: Rho Gtpases At the Nucleus: Trafficking And Functional Impactmentioning
confidence: 96%
“…Rac1-regulated actin dynamics contribute to nuclear membrane organization, which in turn can have an impact on LMNA/C-emerin complex distribution, supporting direct crosstalk between nuclear actin network changes and lamin cortex integrity and remodeling; further, Rho GTPase control of the cytoskeleton is an additional input, through the LINC complex, onto nuclear mechanoadaptation. Current investigations demonstrate that Rac1 induces nuclear alterations through microtubules and LINC complex to promote an invasive phenotype in melanoma cells [168]. Rho GTPases are also involved in the specific control of the perinuclear actin cap, a specialized cytoskeletal structure of fibers contacting the nucleus that regulates both nuclear morphology and re-orientation during front-rear polarization.…”
Section: Rho Gtpases At the Nucleus: Trafficking And Functional Impactmentioning
confidence: 96%
“…In melanoma, selective PI3Kβ inhibitors could inhibit the growth and migration of melanoma cell lines induced by mutant RAC1 43 . Colón-Bolea et al 44 found that RAC1 enhanced melanoma invasiveness by inducing nuclear alterations through the LINC complex. In our study, we validated that the suppression of the RAC1 expression indeed attenuated the proliferation and migration as well as augmented the apoptosis of melanoma cells, which was consistent with the conclusions reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, migration of cells in a LINC complex independent manner or even in a faster rate upon inhibition of the LINC complex was reported for mouse melanoma cells (Fracchia et al, 2020), human lung cancer cells (Lv et al, 2015) and rat mammary adenocarcinoma cells (Sharma et al, 2021). Still, it should be noted that there are other cancer cells that do require the LINC complex to support their migration (Colón-Bolea et al, 2020;Imaizumi et al, 2018;Infante et al, 2018). Interestingly, in parallel there are accumulating reports on down-regulation of LINC complex components in various cancer types such as breast cancer, lung cancer, prostate cancer and liver cancer (Cartwright and Karakesisoglou, 2014;Lv et al, 2015;Marmé et al, 2008;Matsumoto et al, 2015;Sharma et al, 2021;Sur-Erdem et al, 2020;Tessema et al, 2008;Yajun et al, 2017).…”
Section: Linc Complex Independent Cell Migrationmentioning
confidence: 92%